Composing the Uncertainty: Exploring Different Possibilities of Indeterminacy in Composition - Fung, Kai Chung (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2021)
This PhD project Composing the Uncertainty comprised of a portfolio of seven compositions - To Define is to Limit, The Ecstasy of Liberation, Oblivion, Caprice of the Cosmos, String Quartet Part 1, Defining Chaos, and Detour - with the duration of around 80-100 minutes accompanied by commentary. This project aims to 1) explore different possibilities of indeterminacy and uncertainty in music composition, 2) seek a balance between notated and open elements in the score and performance, and 3) develop new notations to encourage improvisation and co-creation from the performers. The written commentary presents the rationale and motivation behind the pursuit of openness in the composition; explains the compositional philosophies including an in-depth discussion of improvisation, indeterminacy, and notations; then describes with references and notation examples on how indeterminacy is being explored and controlled in this portfolio. This analysis consists of four aspects: 1) indeterminate pitch leaving the pitch open but limiting the range, adding interactive direction and interval, and experimenting with physicality; 2) open form manipulating page sequences and using musical fragments, numbered events, and non-linear movement to offer a pathway for chances and choices; 3) time various ways of using bar-lines to allow and control spontaneity in tempo; and 4) image - the implementation of indeterminate and external images into the score. Lastly, the commentary finishes with a description and reflection of the performances of two of the compositions.
APPROVED
Keywords: improvisation; open form; indeterminacy; aleatory; indeterminacy; contemporary music composition